A two-camera based algorithm for 3D reconstruction of a visual scene. Probabilistic approach - Shcherbakov, A. P. (Journal of computer & systems sciences international, 2009)
One of the approaches to the problem of 3D reconstruction, based on the probabilistic identification of matched images patches, without using active illumination sources, is addressed. The source data for the algorithm are the vectors that describe the boundaries of image regions obtained in advance by a procedure of segmentation into parts of a constant color and the subsequent vectorization of the boundaries of regions. The method described in the paper can deal not only with polyhedrons, but also with objects of arbitrary shape.